Youths’ predispositions to learning : case studies within a place of safety (Western Cape, South Africa) - De Waal, Hester Jacoba (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Centre for Higher Education))--University of Stellenbosch, 2010.